2018
DOI: 10.1002/jlb.3ma1217-502r
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine fragment CXCL9(74–103) diminishes neutrophil recruitment and joint inflammation in antigen-induced arthritis

Abstract: This study investigates if treatment with a peptide corresponding to the 30 C-terminal amino acids of CXCL9, CXCL9(74-103), ameliorates joint inflammation in a murine model of antigen-induced arthritis (AIA). AIA was induced in male C57BL/6J mice. Intravenous injection of CXCL9(74-103), simultaneously performed with a tibiofemoral challenge with methylated BSA (mBSA) as antigen in mice immunized with mBSA, diminished the accumulation of leukocytes, in particular neutrophils, in the synovial cavity. The levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
(133 reference statements)
1
20
0
Order By: Relevance
“…CXCL9 bound with high affinity to soluble and cellular GAGs. The longest 30 amino acid peptide, CXCL9 , was the most potent competitor and competed with CXCL8, muCXCL1, muCXCL6, CXCL11, CCL2, and CCL3 for binding to GAGs (174,231,264). This indicated that CXCL9(74-103) may compete with a wide variety of chemokines that belong to different subclasses.…”
Section: Chemokine-derived Gag-binding Peptidesmentioning
confidence: 95%
“…CXCL9 bound with high affinity to soluble and cellular GAGs. The longest 30 amino acid peptide, CXCL9 , was the most potent competitor and competed with CXCL8, muCXCL1, muCXCL6, CXCL11, CCL2, and CCL3 for binding to GAGs (174,231,264). This indicated that CXCL9(74-103) may compete with a wide variety of chemokines that belong to different subclasses.…”
Section: Chemokine-derived Gag-binding Peptidesmentioning
confidence: 95%
“…CXCR3, CXCR4, and CXCR5 enhance Th1 cells, lymphocytes, B cells, and T follicular helper (Tfh) cells into joint, respectively (100,103). However, CXCL9 can diminish neutrophil recruitment of joints (104). As shown in Table 1, inhibitors or antagonists of these targets have shown good results in animals, such as CXCR3, CXCR4, CXCL10, CXCL12, and CXCL13, especially the antibody of CXCL10 (MDX-1100) has entered clinical trials (25) (Figure 2).…”
Section: Chemokine Targetsmentioning
confidence: 99%
“…7,124,125 The group further evaluated the potency of this CXCL9 peptide in antigen-induced arthritis, where it depicted comparable potency in neutrophil influx attenuation and reduced joint and cartilage damage was observed. 126 Another peptide used in cancer therapy is SSTN 92-119 , also called synstatin. For the activation of αvβ3 integrin, which is upregulated in tumor cells, a capture between IGF1R and αvβ3 integrin by syndecan-1 is necessary, which leads to tumor survival.…”
Section: Therapies Targeting Heparan Sulfate Proteoglycans (Car T-cells Bispecific Antibodies T-cell Vaccines Gene Therapy)mentioning
confidence: 99%